Hibridisasi Pendidikan Islam dan Neurosains: Implementasi Paradigma Integrasi Keilmuan dalam Pendidikan Islam - Ainul Yakin, Anugrah; Suyadi (MA'ALIM: Jurnal Pendidikan Islam, 2025)
This study aims to analyze the integration of Islamic education and neuroscience as a hybrid paradigm in contemporary education. Islamic education ontologically emphasizes the unity of the spiritual, intellectual, and physical in the educational process, while neuroscience provides a scientific basis for brain function, emotions, and behavior in learning. Using a descriptive qualitative approach based on literature review, this study found significant intersections between the two in forming a holistic educational paradigm. This hybridization is realized through the development of an educational model that is not only oriented towards intellectual development but also towards the formation of character and spiritual awareness of students. This integration can be implemented through curriculum design, Islamic neuroeducation-based learning strategies, and the strengthening of faith values in pedagogical practice. This study recommends further development in the realm of educational practice, so that the integration of the values of revelation and reason can become the foundation for the transformation of adaptive and transformative Islamic education in the modern era.